2002
DOI: 10.1542/peds.109.5.e82
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Pediatric Primary Care Providers’ Screening and Referral for Early Childhood Caries

Abstract: ABSTRACT. Purpose. Tooth decay is one of the more common diseases of childhood. Slightly >40% of US children are already affected by the time they reach kindergarten. Primary care physicians can play an important role in prevention and control of this disease because of their ready access to this population. Unlike dentists, they see a large percentage of children during their infant and toddler years. However, few studies have been conducted on oral screenings and referrals by primary care physicians or the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 15 publications
5
112
1
6
Order By: Relevance
“…(2) Mothers play an important role in child's development; oral health counseling is especially important for the mother. Gynaecologists, due to frequent contacts with family are in an ideal position to provide guidelines for improving oral health care to the mothers (3,4) Pregnancy is a time when a woman strives to be particularly aware of the need for health. Health information is of much interest to her and her family, and health professionals can more easily motivate her to follow guidelines towards a sound physical health.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Mothers play an important role in child's development; oral health counseling is especially important for the mother. Gynaecologists, due to frequent contacts with family are in an ideal position to provide guidelines for improving oral health care to the mothers (3,4) Pregnancy is a time when a woman strives to be particularly aware of the need for health. Health information is of much interest to her and her family, and health professionals can more easily motivate her to follow guidelines towards a sound physical health.…”
Section: Introductionmentioning
confidence: 99%
“…Pierce et al conducted a 2-hour instruction course for practitioners, and their findings showed that the practitioners diagnosed 70% of children with oral/dental health problems and referred them to dentists. Therefore, sufficient instruction, even for a short time, may increase practitioners' discernment (16). In another study, McCunniff et al found that the number of children referred to dentists by their practitioners was twice as many as children who were not referred to dentists (17).…”
Section: Discussionmentioning
confidence: 99%
“…11,40 Pediatricians can identify children with cavitated lesions with an acceptable level of accuracy, but they are less accurate in identifying and assessing individual risk factors 13,14,44,45 and tend to underrefer. 46,47 Nationally, approximately half of pediatricians screen most patients for caries.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The literature suggests that physicians will adopt these services and provide quality care that is effective in increasing access to preventive services, reducing treatment needs, averting hospitalizations, and lowering Medicaid costs. [14][15][16][17][18][19][20] Studies reporting improved oral health have either provided circumstantial evidence on the basis of administrative claims 18,19 or have not examined comprehensive services, which include fluoride varnish applications. 15 This study extends previous work by evaluating the impact of comprehensive POHS, which includes screening and risk assessment, fluoride varnish applications, and parental oral health counseling, provided in medical offices by nondental providers, on the dental caries experience of children enrolled in North Carolina's (NC's) Medicaid program.…”
Section: What This Study Addsmentioning
confidence: 99%